The Effectiveness of Self-Guided Digital Interventions to Improve Physical Activity and Exercise Outcomes for People With Chronic Conditions: A Systematic Review and Meta-Analysis - Stavric, Verna; Kayes, Nicola M.; Rashid, Usman; Saywell, Nicola L. (Frontiers in Rehabilitation Sciences, 2022)
Objective: The aim of this systematic review was to determine the effectiveness of self-guided digital physical activity (PA) and exercise interventions to improve physical activity and exercise (PA&E) outcomes for people living with chronic health conditions. Digital health interventions, especially those with minimal human contact, may offer a sustainable solution to accessing ongoing services and support for this population. Methods: A comprehensive and systematic search was conducted up to December 2021, through seven databases for randomized trials that evaluated the effect of self-guided web- or internet-based PA interventions on physical activity or exercise outcomes. Included studies had to have interventions with minimal human contact and interaction with participants needed to be automatically generated. All studies were screened for eligibility and relevant data were extracted. Two independent reviewers assessed the risk of bias using the Cochrane risk of bias tool. Standardized mean differences and 95% confidence intervals (CI) were calculated. PA data were pooled, and forest plots were generated. Results: Sixteen studies met the eligibility criteria and included a total of 2439 participants. There was wide variation in health conditions and intervention characteristics in mode and parameters of delivery and in the application of theory and behavioral strategies. Self-reported PA in the intervention group was greater than controls at the end of the intervention (standardized mean difference (SMD) 0.2, 95% CI=0.1, 0.3) and at follow up (SMD 0.3, 95% CI 0.2 to 0.5). The difference in objectively measured PA was small and non-significant (SMD 0.3, 95% CI ‐0.2 to 0.9). All interventions included behavioral strategies and ten of the sixteen were underpinned by theory. Conclusions: Self-guided digital PA&E interventions provided a positive effect on PA immediately after the intervention. An unexpected and positive finding was a sustained increase in PA at follow-up, particularly for interventions where the behavioral strategies were underpinned by a theoretical framework. Interventions with minimal contact have the potential to support sustained PA engagement at least as well as interventions with supervision.